Effect of start injection toward combustion, performances and emision characteristic of B20 biodiesel fuel - Amat Azman, Putera Mohamad Adam (2020)
The utilization of the palm oil-based fuel in biodiesel fuel as alternative fuel for diesel engine has been implemented in Malaysia. However, the utilization of biodiesel is problematic because the low output power is due to incomplete combustion and incorrect vaporization characteristic. In this research, a small compression ignition engine with 320 cc four strokes direct injection has been used to carry out to characterize the combustion of biodiesel fuel. The performance and exhaust emission have been tested with blended B10 biodiesel (10% POME and 90% pure diesel) and compared with B20 biodiesel (20% POME and 80% pure diesel). The engine was tested under full load steady-state conditions at 1800rpm to 3400rpm with variable start of injection strategy (SOI). Experimental performance measurements including exhaust emissions, cylinder pressure, heat release rate, and ignition delay were conducted. As a result, the use of B20 fuel showed a reduction on engine performances; BT (0.3%), BTE (1.44%), increase of BSFC (up to 3.75%) in comparison with B10 fuels at 2400rpm engine speed. Advancing 1°CA BTDC of SOI strategy in B20 fuel is recommended, where observed an improvement of approximately 3.32% (BTE), 3.23% (BSFC) has been recorded. However, advancing the SOI in B20 fuel increases the Rate of Heat Release (ROHR). The in-cylinder pressure value is also reduced with rise of ROPR. The experimental results prove that the start of injection (SOI) strategy of the fuel has an effect on performance and emission where by advancing SOI by 1°CA bTDC improved 3.3% of BTE. Meanwhile, BSFC is reduced by 3.2% with advancing SOI by 1°CA bTDC. The NOX emission was decreased by 35.67% (approximately 10.21 g/kWh) with advancing SOI by 1°CA bTDC compared to the default SOI which is at 14°CA bTDC. Therefore, advancing the SOI has the potential to improve the engine performances compared to B10 fuels.